GLOBALIZATION TRENDS AND THEIR MANIFESTATION IN RELIGIOUS AND IDEOLOGICAL LIFE - Eshkuvatov B. V (TARIXIY TADQIQOTLAR, 2026)
This article provides a scholarly analysis of the essence of contemporary globalization processes, their impact on religious and ideological life, and the ways these processes manifest within the socio-cultural environment. The study examines issues such as the interaction of religious values with global information exchange, transnational ideological influences, the transformation of religious identity, and the activities of new religious movements that have emerged under conditions of globalization. The article also elucidates the impact of globalization on religious stability, the factors of ideological security, and the scholarly foundations of mechanisms aimed at preserving national and spiritual traditions. The findings of the study contribute to a deeper understanding of religious and ideological processes in the context of globalization and to the formation of a scientific approach to their analysis.